Validation of a novel patient reported tool to assess the impact of treatment in erythropoietic protoporphyria: the EPP-QoL - G. Biolcatti; S. Hanneken; E. I. Minder; N. J. Neumann; J. H. P. Wilson; P. J. Wolgen; D. J. Wright; A. J. Lloyd (SpringerOpen, 2021)
Abstract Background A novel treatment has been developed for erythropoietic protoporphyria (EPP) (a rare condition that leaves patients highly sensitive to light). To fully understand the burden of EPP and the benefit of treatment, a novel patient reported outcome (PRO) measure was developed called the EPP-QoL. This report describes work to support the validation of this measure. Methods Secondary analysis of trial data was undertaken. These analyses explored the underlying factor structure of the measure. This supported the deletion of some items. Further work then explored the reliability of these factors, their construct validity and estimates of meaningful change. Results The factor analyses indicated that the items could be summarised in terms of two factors. One of these was labelled EPP Symptoms and the other EPP Wellbeing, based on the items included in the domain. EPP Symptoms had evidence to support its reliability and validity. EPP Wellbeing had poor psychometric properties. Conclusions Based on the analysis it was recommended to drop the EPP Wellbeing domain (and associated items). EPP Symptoms, despite limitations in the development of items, showed evidence of validity. This work is consistent with the recommendations of a task force that provided recommendations regarding the development, modification and use of PROs in rare diseases.